Microbial Safety of Smoothie Drinks from Fresh Bars Collected in Slovakia - Monika Krahulcová; Barbora Micajová; Petra Olejníková; Klára Cverenkárová; Lucia Bírošová (Foods, 2021)
Among the many consumers in Slovakia, smoothies are nowadays gaining popularity. Smoothie drinks are prepared from raw fruits and vegetables. Therefore, their microbiological safety depends on hygiene standards. The aim of this work was to monitor and quantify selected sensitive and antibiotic-resistant microorganisms present in collected smoothies. Twenty analyzed smoothie samples were collected from six food service establishments (fresh bars) in the capital city of Slovakia, Bratislava. Antibiotic-resistant bacteria were found in at least one of each fresh bar. Antibiotic-resistant coliform bacteria prevailed, especially in green smoothies or juices containing more vegetable ingredients. Resistance to ampicillin, ciprofloxacin, tetracycline, chloramphenicol, and gentamicin was observed in the case of coliform bacteria. More than half of the smoothie drink samples did not contain resistant enterococci. On the other hand, vancomycin-resistant enterococci were detected in 20% of samples. The most frequently isolated antibiotic-resistant strains belonged to the Enterobacter spp. or Klebsiella spp. genus. In the last part of the work, the pretreatment effect of smoothie components on the selected microorganisms’ counts in the final product was investigated. Washing ingredients with an aqueous solution of a biocide agent containing silver and hydrogen peroxide proved to be the most effective way to decrease bacterial counts.